Stable Potential Windows for Long‐Term Electrocatalysis by Manganese Oxides Under Acidic Conditions. (14th March 2019) - Li, Ailong; Ooka, Hideshi; Bonnet, Nadège; Hayashi, Toru; Sun, Yimeng; Jiang, Qike; Li, Can; Han, Hongxian; Nakamura, Ryuhei
Abstract: Efficient, earth‐abundant, and acid‐stable catalysts for the oxygen evolution reaction (OER) are missing pieces for the production of hydrogen via water electrolysis. Here, we report how the limitations on the stability of 3d‐metal materials can be overcome by the spectroscopic identification of stable potential windows in which the OER can be catalyzed efficiently while simultaneously suppressing deactivation pathways. We demonstrate the benefits of this approach using gamma manganese oxide (γ‐MnO2 ), which shows no signs of deactivation even after 8000 h of electrolysis at a pH of 2. This stability is vastly superior to existing acid‐stable 3d‐metal OER catalysts, but cannot be realized if there is a deviation as small as 50‐mV from the stable potential window. A stable voltage efficiency of over 70 % in a polymer–electrolyte membrane (PEM) electrolyzer further verifies the availability of this approach and showcases how materials previously perceived to be unstable may have potential application for water electrolysis in an acidic environment.